Systemic transthyretin amyloidosis in a patient with bent spine syndrome. (2nd May 2013) - Rezania, Kourosh; Pytel, Peter; Smit, Laurel J.; Mastrianni, James; Dina, Michelle A.; Highsmith, W. Edward; Dogan, Ahmet
Abstract: Wild-type and mutant transthyretin (TTR) are implicated in systemic amyloidosis (ATTR). Myopathy is a rare complication of ATTR amyloidosis, however no patient with bent spine syndrome secondary to ATTR amyloidosis has been reported so far. We present the first case of bent spine syndrome in a patient with wild-type ATTR amyloidosis who also had concomitant Alzheimer's disease.